-->
Algebra - Radical Expressions
logo for solving-math-problems.com
leftimage for solving-math-problems.com

Algebra - Radical Expressions








































I need to understand the properties of radical expressions and I need to simplify y=1/(2*sqrt(x+3)+sqrt(x+3).

Comments for Algebra - Radical Expressions

Click here to add your own comments

Mar 03, 2011
Algebra - Radical Expressions
by: Staff


The question:

I need to understand the properties of radical expressions and I need to simplify y=1/(2*sqrt(x+3)+sqrt(x+3).


The answer:

There is one right parenthesis missing in your equation.

I think this is what you mean (I added one parenthesis on the far right):

y=1/(2*sqrt(x+3)+sqrt(x+3))

Using the “Distributive Law”, the denominator can be simplified by factoring the sqrt(x+3) out of each term, as follows:

2*sqrt(x+3)+sqrt(x+3) = sqrt(x+3)*(2+1)

= sqrt(x+3)*(3)

Denominator now = 3*sqrt(x+3)

After the denominator has been simplified in this manner, the equation looks like this:

y=1/(3*sqrt(x+3))

The next step is to remove the sqrt(x+3) from the denominator. This is called “rationalizing the denominator”.

Rationalizing the denominator for your equation can be accomplished easily. Simply multiply both the numerator and denominator by sqrt(x+3).

------------------------------------------------
Denominator: Note that sqrt(x+3)*sqrt(x+3) = x+3.
------------------------------------------------

y=1/(3*sqrt(x+3))

y=[1/(3*sqrt(x+3))]*[sqrt(x+3)/sqrt(x+3)]

y=[1*sqrt(x+3)]/[3*sqrt(x+3)*sqrt(x+3)]

y=[1*sqrt(x+3)]/[3*(x+3)]

y=[sqrt(x+3)]/[3*(x+3)]

y=[sqrt(x+3)]/(3x+9)



The final answer is: y=[sqrt(x+3)]/(3x+9)




Thanks for writing.


Staff
www.solving-math-problems.com


Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2014. All rights reserved. Solving-Math-Problems.com